Call Characteristics of Patients Suspected of Transient Ischemic Attack (TIA) or Stroke During Out-of-Hours Service: A Comparison Between Men and Women - Exalto, Lieza G.; van Doorn, Sander; Erkelens, D. Carmen A.; Smit, Karin; Rutten, Frans H.; Kappelle, L. Jaap; Zwart, Dorien L. M. (Frontiers in Neurology, 2021)
Background: In the Netherlands, a digital decision support system for telephone triage at out-of-hours primary care services (OHS-PC) is used. Differences in help-seeking behavior between men and women when transient ischaemic attack (TIA) or stroke is suspected could potentially affect telephone triage and allocation of urgency. Aim: To assess patient and call characteristics and allocated urgencies between women and men who contacted OHS-PC with suspected TIA/stroke. Methods: A cross-sectional study of 1,266 telephone triage recordings of subjects with suspected neurological symptoms calling the OHS-PC between 2014 and 2016. The allocated urgencies were derived from the electronic medical records of the OHS-PC and the final diagnosis from the patient’s own general practitioner, including diagnoses based on hospital specialist’ letters. Results: 546 men (mean age 67.3 ±17.1) and 720 women (mean age 69.6 ±19.5) were included. TIA/stroke was diagnosed in 294 (54%) men (mean age 72.3 ±13.6) and 366 (51%) women (mean age 78.0 ±13.8). In both genders, face-arm-speech-test (FAST) symptoms were common in TIA/stroke (men 78%, women 82%) but also in no TIA/stroke (men 63%, women 62%). Men with TIA/stroke had shorter call durations than men without TIA/stroke (7.10 vs. 8.20 min, p=0.001), while in women this difference was smaller and not significant (7.41 vs. 7.56 min, p=0.41). Both genders were allocated high urgency in 75% of the final TIA/stroke cases. Conclusion: Overall, patient and call characteristics are mostly comparable between men and women, and these only modestly assist in identifying TIA/stroke. There were no gender differences in allocated urgencies after telephone triage in patients with TIA/stroke.